Patient Satisfaction with Provision of Rehabilitation Services at Pakistan Institute of Prosthetic and Orthotic Sciences (PIPOS) Peshawar - Rehman, Zia; Salim, Muhammad; Asif, Shazia (Journal of Prosthetics Orthotics and Science Technology, 2022)
Patient satisfaction with the services provided in a prosthetics and orthotics (P&O) facility has rarely been studied. This study aimed to analyze patient satisfaction regarding the services provided by seven prosthetic & orthotic (P&O) facilities at PIPOS Rehabilitation Services Program (PRSP) Peshawar. One hundred fifty patients from P&O facilities who were fitted with a prosthesis, an orthosis, or another device, were asked to rate the overall services provided and whether they were satisfied with the device provided and its delivery time by answering the questions according to their experience, provided in the questionnaire. In total, 72% of the consumers were satisfied with the service provided and with the delivery time, and 28% were not satisfied because of much time consumption. The overall consumer rating of the service provided by P&O facilities is high and mainly depends on the delivery time. The outcomes on the Patient Satisfaction Questionnaire were moderate. In the future, it is essential to study patient satisfaction more extensively to improve the quality of P&O services in daily practice. Additionally, specific questionnaires need to be developed to measure all prosthetic and orthotic care aspects to improve the services.